N-Acetyl-d-glucosamine kinase and germ-tube formation in Candida albicans - Shepherd, Maxwell G.; M. Ghazali, Hasanah; Sullivan, Patrick A. (Academic Press, 1980)
N-Acetyl-d-glucosamine kinase (GlcNAc kinase, EC 2.7.1.59), the specific enzyme required for the phosphorylation ofN-acetyl-d-glucosamine (GlcNAc) toN-acetylglucosamine 6-phosphate, was found to be an inducible enzyme inCandida albicans. The pattern of GlcNAc kinase induction was examined under conditions where germ-tube formation was elicited and where blastospores metabolized GlcNAc with no change in morphology. There was no change in either the time course or the extent of GlcNAc kinase induction, indicating that this enzyme is not a control point for the dimorphic development inC. albicans. A low basal level of GlcNAc kinase activity was found in noninduced cells ofC. albicans but this increased 20- to 30-fold after the addition of GlcNAc to the cell suspension. GlcNAc is both an inducer and a substrate for the enzyme; ATP and Mg2+ were also required for activity. TheKmvalues for GlcNAc and ATP are 1.9 and 1.3 mm, respectively. ADP was found to be a noncompetitive inhibitor with respect to GlcNAc with aKivalue of 7.1 mm. UDP-GlcNAc and glucosamine 6-phosphate had no effect on GlcNAc kinase activity. The presence of ethidium bromide (an inhibitor of transcription) or trichodermin (an inhibitor of translation) in cell suspensions ofC. albicans inhibited the increase in GlcNAc kinase specific activity. The glucose analogs, α-methylglucopyranoside and 3-O-methylglucose, enhanced the formation of germ tubes byC. albicans but the induction of GlcNAc kinase was not affected. 2-Deoxyglucose, an inhibitor of germ-tube formation, had no effect on the induction of GlcNAc kinase